Case Report: Can Targeted Intraoperative Radiotherapy in Patients With Breast Cancer and Pacemakers be the New Standard of Care? - Bhimani, Fardeen; Johnson, Kelly; Brodin, N. Patrik; Tomé, Wolfgang A.; Fox, Jana; Mehta, Keyur; McEvoy, Maureen; Feldman, Sheldon (Frontiers in Oncology, 2022)
Background Partial breast irradiation with Intra-operative radiotherapy (IORT) has become a popular management option as opposed to whole breast radiation using external beam radiotherapy for breast cancer patients. While previous studies have highlighted the use of IORT in breast cancer patients, there is a scarcity of literature on the use of IORT in those who also have ipsilateral pacemakers. Thus, the aim of our case report is to highlight the applicability of IORT in breast cancer patients who also have a pacemaker. Case Reports Two female patients with an implanted dual-chamber pacemaker presented with a diagnosis of left-sided invasive ductal carcinoma on mammogram. Mammography of the left breast revealed a 10 mm and 7 mm spiculated mass, respectively, further confirmed with an ultrasound-guided core biopsy that was conclusive of clinical Stage I T1 N0 grade 2, ER +, PR + Her2 – invasive ductal carcinoma. They met our eligibility criteria for IORT, which is being performed as a registry trial. These patients underwent a wide excision lumpectomy along with IORT. Conclusion Our findings underscore the successful use of targeted IORT for breast-conserving surgery in a patient with invasive ductal carcinoma and pacemaker, hence eliminating the necessity for relocating pacemaker surgeries in these patients. Furthermore, no device failure or malfunction for the pacemaker was recorded before, during, or after the surgery, demonstrating the safety of using IORT in patients with preinstalled pacemaker despite a lack of evidence on safe radiation dosage or manufacturer guidelines. Nonetheless, the effects of IORT on pacemaker < 10 cm were not studied in our patients and further clinical studies are recommended to reinforce the applicability and safe distance of IORT in breast cancer patients with pacemaker.